2023
DOI: 10.1038/s41598-023-29987-x
|View full text |Cite
|
Sign up to set email alerts
|

Self-administration of a Salmonella vaccine by domestic pigs

Abstract: Hand vaccinating is time consuming and inefficient. Oral vaccines delivered by drenching are less likely to be used due to a lack of labor on farms. Current environmental enrichment (EE) technologies do not allow pigs to express certain natural behaviors such as rooting and getting a reward. We developed a sprayer so that domestic pigs can self-apply any liquid. By adding an attractant (pig maternal pheromone), the use of EE devices by individual pigs can be increased. In this study, we used a Salmonella oral … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…When the trigger sprayer was pressed, the 4 mL liquid was delivered. The functionality of the EE sprayer has previously been used to deliver an oral vaccine [ 5 ]. BB sprayers were also available in the training pens of the BB treatment group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the trigger sprayer was pressed, the 4 mL liquid was delivered. The functionality of the EE sprayer has previously been used to deliver an oral vaccine [ 5 ]. BB sprayers were also available in the training pens of the BB treatment group.…”
Section: Methodsmentioning
confidence: 99%
“…Prior to this field study, we developed an environmental enrichment (EE) sprayer with which gilts could self-administer any liquid at will [ 5 ], such as vaccines and pheromones. In earlier work with sows, we found that pregnant sows would use the sprayer one to two times per day on average, whereas sows in estrus averaged 17 sprays per day (unpublished work in preparation).…”
Section: Introductionmentioning
confidence: 99%